Physical, Chemical and Mechanical Characterization of Sida Rhombifolia Fibers from the Center Region of Cameroon for their potential use in textiles and composites - Téclaire Ngoup; Nkemaja Dydimus Efeze; Thomas Kanaa; Jonas Peequeur Essome Mbang; César Segovia; Nnanga Nga; Ebenezer Njeugna (Journal of Natural Fibers)
To substitute synthetic fibers, which are non-biodegradable and environmentally unfriendly, studies have been carried out to exploit vegetable fibers. Within this concept, this work investigates Sida rhombifolia as a case study. Previous studies showed that the fibers could be extracted only by cold water retting, but this study seeks to show that the boiling water extraction technique can also be used. The objective of this study is to characterize Sida rhombifolia fibers from the Center region of Cameroon, extracted with cold and boiling water, and compare their physico-chemical and mechanical properties with those of other vegetable fibers. The standard tests for the different characterizations have been respected. This study showed that the fibers extracted with cold water retting contained 70.16% cellulose, 16.70% hemicellulose, 10.86% lignin, and 1.47% pectin, while the fibers extracted by boiling water technique contained 68.71% cellulose, 17.48% hemicellulose, 11.26% lignin, and 2.01% pectin. Finally, extraction of fibers from the cold water retting technique gave 38.83% extraction yield, 1.33 g.cm−3 density, 11.23 tex linear mass, 11.73% water content, 118.53% rate of water absorption, and 21.45% humidity at a relative humidity of 75%. While fibers extracted by the boiling water technique had 33.74% extraction yield, 1.35 g.cm−3 density, 13.57 tex linear mass, 13.28% water content, 225.12% rate of water absorption, and 22.06% humidity at a relative humidity of 75%, statistical analysis by Student’s t-test showed a significant difference in the mechanical properties of the fibers depending on the extraction method. Sida rhombifolia fibers can be used in textiles and composites and can be extracted by the boiling water technique.